A CMOS ISFET interface circuit with dynamic current temperature compensation technique - Chan, Pak Kwong (2009)
This paper presents a new ion-sensitive field-effect transistor (ISFET ) readout circuit including a novel nonlinear temperature compensation method that is based on the theoretical work for formulating a body-effect-based ISFET drain current expression, the derivation of an unified temperature-dependent ISFET threshold voltage expression, and the use of iterative method for solving design parameters in nonlinear equations. Regarding the basic readout circuit, it comprises only one source follower and one current source to establish a self-biased configuration